2018
DOI: 10.18203/issn.2455-4529.intjresdermatol20181818
|View full text |Cite
|
Sign up to set email alerts
|

A study of verapamil in treatment of keloid

Abstract: <p class="abstract"><strong>Background:</strong> Keloid is a common presentation in clinical practice. Symptoms due to keloid are mild, but disfigurement and functional impairment can be severe. It is difficult to treat. Intralesional, injection triamcinolone acetonide, has limited efficacy, causes adverse effects such as local dermal atrophy, telengiectasia and hypopigmentation. Injection verapamil is reported to have similar efficacy, but lesser side effects, and is cheaper. Aim was to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…In our study, the most common side effect was pain at the site of injection as it was reported in 36 keloids (83.7%), this finding was in agreement with that of previous studies 17,20,21 …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our study, the most common side effect was pain at the site of injection as it was reported in 36 keloids (83.7%), this finding was in agreement with that of previous studies 17,20,21 …”
Section: Discussionsupporting
confidence: 93%
“…19 Another study demonstrated that In our study, the most common side effect was pain at the site of injection as it was reported in 36 keloids (83.7%), this finding was in agreement with that of previous studies. 17,20,21 In our study, recurrence was observed in 9 keloids (20.9%), which was in agreement with the results obtained by a previous study com-…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…28,29 An open label study found that there is a significant decrease in VSS score after administration of intralesional verapamil within 8 months (p<0.001) with no complaint of post-procedural pain experienced. 30 However, reasons why verapamil remain as second-line treatment in keloid management needs to be further discussed.…”
Section: Guidelines On Treatment Of Keloids According To Thementioning
confidence: 99%